Bequest intent and the moderating impact of estate planning and self-control on wealth composition: a tax perspective - Strong, C. Ramel (Kansas State University, 2023)
While the relationship between bequest motive and wealth accumulation has been the focus of previous research, less is known about the relationship between bequest motive and wealth composition Specifically, no research has been done to assess how bequest intent impacts the percentage of assets older adults hold in taxable assets e.g. investment accounts, real estate, and businesses, versus tax-deferred accounts, primarily qualified retirement plans and Individual Retirement Accounts (IRAs) This decision is critical as it can impact the amount of assets future generations assets receive on an after-tax basis. This dissertation examines the relationship between bequest intent and wealth composition, utilizing estate planning and self-control as moderating variables. These two factors are important as they represent external and internal tools, respectively, for translating bequest intent into action. This study utilizes an empirical model based on the behavioral life cycle hypothesis (BLCH), which has been utilized to study saving and dissaving behavior. The study used data from the 2018 wave of the Health and Retirement Study (HRS). Utilizing a censored regression technique, the study analyzed the relationship between demographic, life cycle, and bequest-related factors and the percentage of total portfolio assets held in taxable accounts. The model found there to be a positive relationship in general between bequest intent and the percentage of portfolio assets in taxable accounts. In addition, self-control and a family history of estate planning were found to have a positive relationship with the percentage of assets held in taxable accounts; estate planning did not have a statistically significant relationship. No evidence was found to support a moderating effect for estate planning or self-control. The target audience for this study is financial planners, counselors, and attorneys, with implications that can help highlight the importance of understanding bequest intent, managing and increasing self-control, and building a family legacy of estate planning.
Keywords: Bequest intent; Estate planning; Self-control; Behavioral life-cycle hypothesis; Wealth composition